Triggers ebook Creating behavior that lasts—becoming the person you want to be. - Goldsmith, Marshall (2015)
Bestselling author and world-renowned executive coach Marshall Goldsmith examines the environmental and psychological triggers that can derail us at work and in life. Do you ever find that you are not the patient, compassionate problem solver you believe yourself to be? Are you surprised at how irritated or flustered the normally unflappable you becomes in the presence of a specific colleague at work? Have you ever felt your temper accelerate from zero to sixty when another driver cuts you off in traffic? Our reactions don’t occur in a vacuum. They are usually the result of unappreciated triggers in our environment—the people and situations that lure us into behaving in a manner diametrically opposed to the colleague, partner, parent, or friend we imagine ourselves to be. These triggers are constant and relentless and omnipresent. So often the environment seems to be outside our control. Even if that is true, as Goldsmith points out, we have a choice in how we respond. In Triggers , his most powerful and insightful book yet, Goldsmith shows how we can overcome the trigger points in our lives, and enact meaningful and lasting change. Goldsmith offers a simple “magic bullet” solution in the form of daily self-monitoring, hinging around what he calls “active” questions. These are questions that measure our effort, not our results. There’s a difference between achieving and trying; we can’t always achieve a desired result, but anyone can try. In the course of Triggers , Goldsmith details the six “engaging questions” that can help us take responsibility for our efforts to improve and help us recognize when we fall short. Filled with revealing and illuminating stories from his work with some of the most successful chief executives and power brokers in the business world, Goldsmith offers a personal playbook on how to achieve change in our lives, make it stick, and become the person we want to be.